1997
DOI: 10.1149/1.1837643
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Prediction of the Scan Rate Dependencies of the Pitting Potential and the Probability Distribution in the Induction Time

Abstract: The point defect model (PDM) has been used to derive the dependence of the pitting potential on the voltage scan rate. Relationships derived from the PDM predict that the observed pitting potential is a linear function of the square root of voltage scan rate at low scan rates, which agrees with experimental data reported in the literature. Furthermore, the critical concentration of condensed cation vacancies that give rise to passivity breakdown, as estimated from the sweep rate dependence of the pitting poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 0 publications
7
47
0
8
Order By: Relevance
“…In fact, longer polarisations must lead to pits of higher size, consequently, of more difficult repassivation. A plot of the breakdown potentials, E b , as a function of the square root of the scan rate is in agreement with the point defect model (PDM) of MacDonald [11]. The slope of the straight line presents a value of 0.35 (Vs) 1/2 identical to the value obtained in a previous study of Al2024 in seawater solution [30].…”
Section: The Transpassive Regionsupporting
confidence: 86%
See 1 more Smart Citation
“…In fact, longer polarisations must lead to pits of higher size, consequently, of more difficult repassivation. A plot of the breakdown potentials, E b , as a function of the square root of the scan rate is in agreement with the point defect model (PDM) of MacDonald [11]. The slope of the straight line presents a value of 0.35 (Vs) 1/2 identical to the value obtained in a previous study of Al2024 in seawater solution [30].…”
Section: The Transpassive Regionsupporting
confidence: 86%
“…Cyclic voltammetry allows the identification of the various oxidation/reduction processes that occur at the electrode/solution interface during the cyclic polarisation. It also allows testing the applicability of models, i.e., the model of the breakdown of passivity, known as the Point Defect Model (PDM) established by MacDonald et al [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-understood that the passivity breakdown potential often depends on the method of its determination and, in particular, on the potential scan rate [8] when determined potentiodynamically. Also, several researchers [8,[43][44][45][46][47] have found that the more noble the potential is held, the shorter is the time required for pit initiation. Accordingly, when the potential scan rate is high, a rapid increase in current density can only be observed at more positive (noble) potentials, in compensation for the shorter time that is available for breakdown.…”
Section: Resultsmentioning
confidence: 99%
“…Several papers reported that E p was affected by potential sweep rate. Macdonald [12][13][14] pointed out that on the basic of the point defect model (PDM) a relationship between pitting potential and potential sweep rate existed. In parallel, the pitting potential was a linear function of the square root of potential sweep rate at low sweep rates.…”
Section: Introductionmentioning
confidence: 99%